2018
DOI: 10.4102/sajems.v21i1.2030
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of organisational culture using CiteSpace

Abstract: Background: As organisational culture plays an important role in forming a sustained competitive advantage, numerous studies about organisational culture have been completed. However, few studies have been conducted by analysing the references of publications with a visual pattern. Moreover, this subject has reached a certain degree of maturity; hence, a review that analyses the trends of organisational culture is urgent. Aim: The aim of this study was to provide broad information on organisational culture, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…And the thematic analysis of our review also demonstrated the emphasis of NBS studies on greening and sustainable urban development in recent research. A large number of publications were coupling NBS and climate change together through the functions of NBS to improve risk management and resilience in urban areas [56]. More recently, the focus has been shifted to greening in urban areas, such as urban forests than disaster risk reduction.…”
Section: Results Types For Research Objectives Results Details Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the thematic analysis of our review also demonstrated the emphasis of NBS studies on greening and sustainable urban development in recent research. A large number of publications were coupling NBS and climate change together through the functions of NBS to improve risk management and resilience in urban areas [56]. More recently, the focus has been shifted to greening in urban areas, such as urban forests than disaster risk reduction.…”
Section: Results Types For Research Objectives Results Details Research Implicationsmentioning
confidence: 99%
“…This study employed an extensive search strategy to locate relevant published studies by a computer search. The Web of Science (WOS) was used because it is the largest and inclusive academic database with more than 8700 core academic journals and seven databases [56,57]. WOS provides a platform to share comprehensive, formats uniformed, and academic references.…”
Section: Data Collection and Identificationmentioning
confidence: 99%
“…It can perform co-authorship analysis, cocitation analysis, co-word analysis, and co-occurrence analysis (C. Chen, 2006). Because of its powerful functions and simple operation, it has recently become one of the most widely used Atlas software packages (Cui et al, 2018;Hu et al, 2013;Li et al, 2017).…”
Section: Methodology and Datamentioning
confidence: 99%
“…CiteSpace has been used to visualize science and technology (Liu, 2013), geography (Wang and Liu, 2014; Wei et al, 2015), social commerce (Cui et al, 2018b) and organizational culture (Cui et al, 2018a). However, CiteSpace has not been used to analyse/compare rapidly expanding sociology of sport literatures.…”
Section: Methodsmentioning
confidence: 99%